2010
DOI: 10.1007/s10059-010-0050-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and cDNA Cloning of a Cecropin-Like Antimicrobial Peptide, Papiliocin, from the Swallowtail Butterfly, Papilio xuthus

Abstract: Cecropin is a well-studied antimicrobial peptide that is synthesized in fat body cells and hemocytes of insects in response to hypodermic injury or bacterial infection. A 503 bp cDNA encoding for a cecropin-like peptide was isolated by employing annealing control primer (ACP)-based differential display PCR and 5'-RACE with immunized Papilio xuthus larvae. The open reading frame of the isolated cDNA encoded for a 62-amino acid prepropeptide with a putative 22-residue signal peptide, a 2-residue propeptide, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 22 publications
1
62
0
Order By: Relevance
“…expression by annealing control primer (ACP)-based differential display PCR (Kim et al, 2010). Up-expressed genes in immune challenged larvae ACP-based PCR were conducted using 120 pairs of arbitrary ACPs and dT-ACP2 to synthesize the second-strand cDNA.…”
Section: Resultsmentioning
confidence: 99%
“…expression by annealing control primer (ACP)-based differential display PCR (Kim et al, 2010). Up-expressed genes in immune challenged larvae ACP-based PCR were conducted using 120 pairs of arbitrary ACPs and dT-ACP2 to synthesize the second-strand cDNA.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, cecropins have also been isolated from several orders of insects such as lepidopteran, dipteran, coleopteran (Kim et al, 2010;Liang et al, 2006;Kylsten et al, 1990;Morishima et al, 1990). …”
Section: Reverse Transcription Pcr (Rt-pcr)mentioning
confidence: 99%
“…The sequences of cecropins have basic residues in N-terminal segments and hydrophobic residues in their C-terminal segments. They have a broad spectrum of activity againstGram-negative and Gram-positive bacteria as well as certain fungi and metazoan parasites (Chalk et al, 1995;DeLucca et al, 1997), but they have little effect on normal eukaryotic cells.Previously, a 37-residue cecropin-like peptide named papiliocin was isolated from the bacteria-immunized larvae of the swallowtail butterfly Papilio xuthus (Kim et al, 2010). This peptide was shown significant antimicrobial activities against both human pathogenic bacterial and fungal strains, and also evidenced no hemolytic activity against human red blood cells.…”
mentioning
confidence: 99%
“…[5][6][7] Studies of innate immune systems of insects have shown the importance of AMPs for the defense of these organisms against bacteria. 7,8 In insects, over 200 AMPs have been identified. Papiliocin, with 37-residues (RWKIFKKIEKVGRNVRDGIIKAGPA VAVVGQAATVVK-NH2) has been isolated from the larvae of the swallowtail butterfly, Papilio xuthus, and it belongs to a cecropin family that have strong antibacterial activities against Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Papiliocin, with 37-residues (RWKIFKKIEKVGRNVRDGIIKAGPA VAVVGQAATVVK-NH2) has been isolated from the larvae of the swallowtail butterfly, Papilio xuthus, and it belongs to a cecropin family that have strong antibacterial activities against Gram-negative bacteria. 8 We studied the structure of papiliocin by NMR spectroscopy and the structure shows that papiliocin has an α-helical structure from Lys 3 to Lys 21 and from Ala 25 to Val 35 , linked by a hinge region, in 300 mM dodecylphosphocholine (DPC) micelles. 9 In order to understand the structural requirements for papiliocin function and to design shorter and potent peptide antibiotics, we designed papiliocin analog, PapN (residues Arg 1 -Ala 22 from the N-terminal amphipathic helix).…”
Section: Introductionmentioning
confidence: 99%